Endoscopic lithotripsy with a SuperPulsed thulium‐fiber laser for ureteral stones: A single‐center experience. (30th November 2020) - Enikeev, Dmitry; Grigoryan, Vagarshak; Fokin, Igor; Morozov, Andrey; Taratkin, Mark; Klimov, Roman; Kozlov, Vasiliy; Gabdullina, Svetlana; Glybochko, Petr
Abstract : Objectives: To estimate the efficacy and safety of SuperPulsed thulium‐fiber laser ureteral lithotripsy and to identify optimal laser settings. Methods: Patients with solitary stones were prospectively included. Lithotripsy was performed with a SuperPulsed thulium‐fiber laser (NTO IRE‐Polus, Fryazino, Russia) using a rigid ureteroscope 7.5 Ch (Richard Wolf, Knittlingen, Germany). We analyzed the efficacy of lithotripsy by measuring total energy required for stone disintegration, "laser‐on" time, ablation speed, ablation efficacy, and energy consumption. Stone retropulsion and visibility were assessed using a three‐point Likert scale. Complications were assessed using the Clavien–Dindo classification system. Results: A total of 149 patients were included. The mean stone density was 985 ± 360 Hounsfield units, the median (interquartile range) stone volume was 179 (94–357) mm 3 . The median (interquartile range) total energy was 1 (0.4–2) kJ, and laser‐on time 1.2 (0.5–2.7) min. The median (interquartile range) stone ablation speed was 140 (80–279) mm 3 /min, energy for ablation of 1 mm 3 was 5.6 (3–9.9) J/mm 3 and energy consumption was 0.9 (0.6–1) J/min. A correlation was found between retropulsion and the energy used ( r = 0.5, P < 0.001). Multivariable analysis showed energy to be a predictor of increased retropulsion (odds ratio 65.7, 95% confidence interval 1.6–2774.1; P = 0.028). No predictors for worse visibility were identified. Conclusion: The SuperPulsed thulium‐fiber laser provides effective and safe lithotripsy during ureteroscopy regardless of stone density. Fiber diameter and laser frequency do not influence visibility or safety. Optimal laser settings are 0.5 J × 30 Hz for fragmentation and 0.15 J × 100 Hz for dusting.